1984/ George Orwell - Orwell,George; Orwell,George 1903-1950 (Karachi Liberty Books, 2023)
The book is set in 1984 in Oceania, one of three perpetually warring totalitarian states (the other two are Eurasia and Eastasia). Oceania is governed by the all-controlling Party, which has brainwashed the population into unthinking obedience to its leader, Big Brother. The Party has created a propagandistic language known as Newspeak, which is designed to limit free thought and promote the Party$1 (Bs doctrines. Its words include doublethink (belief in contradictory ideas simultaneously), which is reflected in the Party$1 (Bs slogans: (3z(BWar is peace,(3y z(BFreedom is slavery,(3y (Band (3z(BIgnorance is strength.(3y (BThe Party maintains control through the Thought Police and continual surveillance. Textbook chalkboard and apple. Fruit of knowledge. Hompepage blog 2009, History and Society, school education students Britannica Quizs
This book is written by Eric Arthur Blair ( 1903-1959 )who used George Orwell as his pen name.
Keywords: Totalitarianism-Fiction -- London (England)